Locality Shaping the Institution: Genesis Connection Youth Skills Multimedia, Riverlea, Johannesburg - Pather, Jodie (University of the Witwatersrand, Johannesburg, 2024)
Following the rich history that community art centres have had in South Africa, this research questions how locality may ideologically shape community-based arts institutions and have a bearing on how they operate and what they have access to. Specifically, this study looks at the community-based arts organisation, Genesis Connection Youth Skills Multimedia (Genesis), in Riverlea, Johannesburg. This research report is carried out to ascertain the extent to which Genesis and the work that they do is influenced by their home community of Riverlea, and how this locality may affect or determine their curriculum, programming, and access to funding. Through episodic interviews, I explore the significance of locality to community-based art centres as is experienced directly by facilitators of different initiatives. The first chapter in this report deals with an overview of scholarship on community art centres; defining and contextualising them, including a historical overview of community art centres that have existed in Johannesburg. Locality, as a concept and its associated literature as related to community art centres is discussed and incorporates perspectives from facilitators working in the field. The second chapter presents a historical overview of the area of Riverlea and builds on the description from Chris Van Wyk’s autobiographical work Shirley, Goodness and Mercy (2004), as a way of complementing, enriching and humanising the academic perspectives on the area of Riverlea. These upfront chapters provide the context for the birth of Genesis, and the terrain that it operates in. Lastly, the third chapter looks at the funding landscape that has sustained community-based arts in South Africa, with specific attention paid to government-funded community-based arts centres, alongside a discussion of how Genesis is funded. The purpose of this is to establish an understanding of the accessibility of funds for arts organisations, what their unique challenges may be, as well as to highlight the sustainability of government-funded organisations in comparison to that of self funded organisations, such as Genesis
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: Community-based arts; Locality; Genesis Connection Youth Skills Multimedia; Riverlea; UCTD; SDG-4: Quality education